Efecto del sobrenadante del cultivo de Bifidobacterium ani'znalis subsp. Lactis sobre la supervivencia del Salmonella typhi - Abad Castillo, Jonatan Cristhian (2014)
In this study we evaluated the bactericida! effect of the culture supematant of_x000D_ Bifidobacterium animalis subsp Lactis on the survival of Salmonella typhi. Three_x000D_ systems for evaluation were prepared- two of which served as a control consisting of_x000D_ MRS broth pH 7 and MRS broth pH 4, and a problem system consisting of the_x000D_ supematant obtained from B. animalis subsp. Lactis. lmL of the inoculum of 3 x 108_x000D_ cells 1 mL of S. typhi was added to each of the three systems, which were then incubated_x000D_ at 37 oC for 24 hours. Starting at zero hours and then every three hours thereafter for a_x000D_ total of 24 hours, the survival of S. typhi was monitored by the plate count method, by_x000D_ measuring the planting and incorporating of the cells. The results show a decrease in_x000D_ colony forming units (CFU 1 mL) of S. typhi after 24 hours of assessment under_x000D_ refrigeration. So it is concluded that B. animalis subsp Lactis does affect the survival of_x000D_ S. typhi in refrigerated conditions.